Effect of platelet large cell ratio (PLCR) and immature granulocyte (%IG) values on prognosis in surgical site infections - Kılıç, Berna Şermin; Atakul, Nil (Journal of Surgery and Medicine, 2021)
Background/Aim: Surgical site infections (SSI) are serious operative complications that occur in approximately 2% of surgical procedures, although rates vary widely according to the type of procedure. Measurement of immature granulocyte percentage (%IG) and Platelet Larger Cell Ratio (PLCR) may be used as a marker of serious bacterial infections. The study aims to evaluate whether the %IG and PLCR are useful additional predictive markers of surgical site infections. Methods: This retrospective cohort study included 50 patients with surgical site infections and 50 control individuals. Patients who were hospitalized in the Istanbul Education and Research Hospital Gynecology and Obstetrics Department between October 2017 and January 2019 were scanned. The Mann-Whitney U test was used to compare continuous variables, and the chi-square test was utilized to compare categorical data. Results: A cut-off of 30.1 for PLRC and 0.35 for %IG had 72% sensitivity and 45% specificity, and 97% sensitivity and 78% specificity (AUC: 0.95), respectively, for the diagnosis of wound site infections. The PLRC and %IG values of the patients with and without wound site infections significantly differed (P=0.052, and P<0.05, respectively). PLRC value slightly negatively correlated with hospitalization duration (r = -0.102), and strongly negative correlated with antibiotic use (r = -0.01). Conclusion: PLCR and %IG can be used as easy, reliable, cost-effective, and fast biomarkers for the detection and evaluation of severity in wound infection.